TAK-003 Dengue Vaccine Efficacy and Safety: A Systematic Literature Review Using PRISMA - Galih Muchlis Hermawan; Syuharul Qomar; Iga Putri Imansari (Indonesian Journal Publisher, 2026)
Background: Dengue is a global public health problem with a high disease burden in both endemic and non-endemic regions. Although dengue vaccines have been developed, evidence regarding the efficacy and safety of the TAK-003 vaccine remains fragmented, with variations across serotypes, age groups, baseline serostatus, and study designs. Objective: This study aims to analyze and synthesize scientific evidence on the efficacy and safety of the tetravalent dengue vaccine TAK-003 based on clinical trial data and real-world evidence. Methods: A Systematic Literature Review was conducted in January 2025 in accordance with PRISMA guidelines. Literature searches were performed in the ScienceDirect, PubMed, ProQuest, and ClinicalKey databases, yielding a total of 1,011 initial records. After duplicate removal, title and abstract screening, and full-text eligibility assessment, studies were included if they: (1) explicitly investigated TAK-003, (2) reported outcomes related to efficacy, immunogenicity, and/or safety, (3) employed clinical trial, observational, or post-marketing surveillance designs, and (4) were available as full-text articles in English. Non-empirical studies, animal studies, commentaries, and narrative reviews were excluded. Results: Five high-quality articles from Scopus Q1 journals met the inclusion criteria. The thematic analysis identified five main themes: the safety and immunogenicity of TAK-003 when co-administered with other vaccines, manufacturing consistency with stable immune responses, long-term effectiveness in preventing dengue infection and hospitalization for up to 4.5 years, tetravalent protection against all four dengue serotypes, and a favorable safety profile based on post-marketing data, with most adverse events being mild. Conclusion: The TAK-003 vaccine demonstrates favorable efficacy and safety profiles in both clinical trials and real-world settings. Although variability in effectiveness across serotypes and age groups persists, the available evidence supports TAK-003 as a promising strategy for dengue prevention.